Development of Intelligent Interface to Input and Edit Meteorological Data; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Shamin A. A. Aleksey Alekseevich (2017, 2017)
Title screen